The Formation And Development Of Horse-Keeping In The History Of Turan - Kadirova Mamlakat Muminovna (Genius Journals, 2025)
The article analyzes the emergence, development and role of horse-breeding in the life of society in the Turan region. The importance of horse-breeding in animal husbandry, military affairs, transport and cultural ceremonies from the earliest times is highlighted. Based on ancient written sources, archaeological finds and ethnographic data, the experiences of the Turan peoples in horse breeding, domestication of wild breeds and the art of horse riding are revealed. The role of horse-breeding in economic, social and cultural development and its continued traditions in modern times are also analyzed
Keywords: Turan; history of horse-breeding; animal husbandry